Ultra high pressure homogenization (UHPH) inactivation of Bacillus amyloliquefaciens spores in phosphate buffered saline (PBS) and milk - Dong, Peng; Georget, Erika S.; Aganovic, Kemal; Heinz, Volker; Mathys, Alexander (Frontiers in Microbiology, 2015)
Ultra high pressure homogenization (UHPH) opens up new areas for dynamic high pressure assisted thermal sterilization of liquids. Bacillus amyloliquefaciens spores are resistant to high isostatic pressure and temperature and were suggested as potential surrogate for high pressure thermal sterilization validation. B. amyloliquefaciens spores suspended in PBS buffer (0.01 M, pH 7.0), low fat milk (1.5%, pH 6.7) and whole milk (3.5%, pH 6.7) at initial concentration of ~106 CFU/mL were subjected to UHPH treatments at 200, 300 and 350 MPa with an inlet temperature at ~80 °C. Thermal inactivation kinetics of B. amyloliquefaciens spores in PBS and milk were assessed with thin wall glass capillaries and modeled using mechanistic linear first order and Weibull models. The residence time during UHPH treatments was estimated to determine the contribution of temperature to spore inactivation by UHPH. No sublethal injury was detected after UHPH treatments using sodium chloride as selective component in the nutrient agar medium. The inactivation profiles of spores in PBS buffer and milk were compared and fat provided no clear protective effect for spores against treatments. Treatment at 200 MPa with valve temperatures lower than 125 °C caused no reduction of spores. A reduction of 3.5 log10 CFU/mL of B. amyloliquefaciens spores was achieved by treatment at 350 MPa with a valve temperature higher than 150 °C. The modeled thermal inactivation and observed inactivation during UHPH treatments suggest that temperature could be the main lethal effect driving inactivation.